Chromosomal Mutagenesis (Second Edition) - Pruett-Miller, Shondra M (Humana Press, 2015)
The era of genomics has ushered in exciting new opportunities for scientists to not only better understand biology but also to enhance biology. Although it has been over a decade since the human genome was fully sequenced, the tools needed to precisely and effectively make targeted genomic modifications have only recently become efficient and available. Through chromosomal mutagenesis, we now have the potential to create cell and animal based models that have and will continue to become essential not only in the field of basic research but also in drug development, personalized medicine, and even food production. In this edition of Chromosomal Mutagenesis, we provide comprehensive coverage and detailed protocols on current and emerging mutagenesis methods focusing specifically on mammalian systems and commonly used model organisms...